EFEKTIVITAS VERMIKOMPOS EISENIA FOETIDA SAVIGNY DALAM MEMPERBAIKI TINGKAT PRODUKSI DAN KUALITAS NUTRISI Sorghum bicolor (L.) Moench DAN Centrosema pubescens Benth - Permana, Asep Tata; Abdullah, Luki; Karti, Panca Dewi Manuhara; Toharmat, Toto; Suwarno, Suwarno (Pastura, 2017)
Vermicomspost is an organic product resulted from metabolism process of soil worm like Eisenia foetida Savigny. The experiment was conducted to evaluate the effectivity of vermicompost derived from E. Foetida Savigny in improvement of growth, biomass production and quality of Sorghum bicolor (L.) Moench and Centrosema pubescencs. The results showed that application of vermicompost effectively improved growth, biomass production and N, P, K content of above ground biomass of those experimental plants. Keywords : vermicompost, productivity, quality.